EMPOWERING STUDENT READING SKILLS THROUGH GUIDED READING SESSION FOR SENIOR HIGH SCHOOL - Isabella, Putri; Wahyuni, Nadia Nur; Shoimah, Hikmatus; Zainuddin, Zainuddin (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study explores The ability to read effectively is a fundamental skill that significantly influences students’ academic performance and overall language development, particularly at the senior high school level where students are expected to engage with complex texts across various subjects. However, many students continue to struggle with reading comprehension, vocabulary acquisition, and critical thinking, often due to traditional, one-size-fits-all instructional methods that fail to address individual learning needs. This study investigates the implementation of guided reading sessions as a strategic intervention to empower students’ reading skills in senior high school settings. Guided reading, which involves small-group, leveled instruction, allows teachers to provide targeted support, adapt teaching to students’ proficiency levels, and foster active participation in reading activities. Using a qualitative descriptive approach, data were collected through classroom observations, student interviews, and reading performance assessments over the course of the intervention. The findings indicate that guided reading sessions significantly enhance students’ reading fluency, comprehension, and engagement by creating a supportive, student-centered environment. Furthermore, the collaborative aspect of guided reading encourages peer interaction and builds reading confidence. This research concludes that guided reading is an effective pedagogical strategy for promoting literacy growth and student empowerment. The study offers practical recommendations for educators seeking to implement guided reading in diverse classrooms and highlights the need for further research to refine its application in secondary education